PENGARUH PERGAULAN TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA DI MTs PONDOK PESANTREN SYAFA’ATURRASUL BATU AMPAR BERINGIN TELUK KUANTAN - Resti Yuliana; Sarmidin Sarmidin; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
This research ismotivated by a problem found in the initial observations of the author at MTs Pondok Pesantren Syafa’aturrasul Batu Ampar Beringin Teluk Kuantan, symptoms are found as follow. 1. Student are less intorested in leraning so student motivation is low. 2. Students are extrovert and lack of making friend with their peers. 3. Their are differencs in backgroud their is a lack of interaction among students. This study aims to determine the effeck of peer interaction on student motivation in MTs Pondok Pesantren Syafa’aturrasul Batu Ampar Beringin Teluk Kuantan. Data collection is accomplished by using observation, interview, questionnaire, and documentation. Writer also used assosiative causal and simple linier regression to analize data. This research had 41 samples. Me analize data with giving explanation about the influences of peer learning MTs Pondok Pesantren Syafa’aturrasul Batu Ampar Beringin Teluk Kuantan. Based on the data and forms show that it has a significant effect to students’s leraning motivation. Indext t is 3,597 > t tabel 1.690. so Ha is received and Ho is rejected. The determinant paint is 0,249 or 24,9%. So the point of influences of peer learning on students’s leraning motivation is 24,9% Kata Kunci : Pergaulan Teman Sebaya, Motivasi belajar siswa.